ANALISIS MIKROSTRUKTURAL DAN MAKROSTRUKTURAL PADA WACANA PENGUMUMAN KORAN KOMPAS EDISI 2 DESEMBER 2024 - Doni Uji Windiatmoko (Indonesian language and literature education program Majapahit Islamic University, 2024)
This study aims to describe the microstructural and macrostructural analysis in the discourse of the Announcement of Recruitment Fraud in the Name of PT Kao Indonesia published in Kompas on December 2, 2024. The results of this study are theoretically useful for providing enlightenment regarding the discourse analysis model for one form of discourse contained in newspapers and is practically useful for providing meaningful contributions in terms of learning to write, especially writing announcements more precisely. This research is descriptive. Based on the microstructural analysis of the announcement discourse, grammatical cohesion was found in the form of cataphoric endophoric references, clause substitution, ellipsis, and causal, combination, choice, and purpose conjunctions. Lexical cohesion is indicated by repetition (repetition) of anaphora and synonymy (equivalent words) of words and phrases. Based on the macrostructural analysis, in understanding the context of the situation and culture, the principles of personal interpretation, the principle of locational interpretation, and the principle of temporal interpretation were found. Meanwhile, the context that accompanies understanding inference is physical context, epistemic context, and social context. Keywords : discourse, announcement, microstructural, macrostructural